Early Triassic initial collision between the North China and South China blocks in the eastern Qinling Orogenic Belt - Ma, Qianli; Yang, Jianghai; Du, Yuansheng; Dai, Xianduo; Chai, Rong; Guo, Hua; Xu, Yajun (Tectonophysics, 2021)
The closure of Mianlue Ocean lead to the collisional assembly between the North China Block (NCB) and the South China Block (SCB). But the timing of initial continental collision remains unclear, with the proposed ages ranging from the Late Permian to the Late Triassic. This study presents stratigraphic, sedimentological, tectonic subsidence, and provenance data from the Triassic strata in the Zigui and Dangyang basins lying along the eastern Qinling Orogenic Belt. These data document a tectonic transition in the central northern-SCB, and locally provide constraints on the timing of initial SCB–NCB collision. The Lower Triassic Daye Formation was deposited in a marginal basin to slope environment, and consists of mudrocks containing detrital zircons with major age peaks at ca. 1900 and 850 Ma. The overlying Lower Triassic Jialingjiang Formation comprises a shallowing carbonate sequence, with intercalated evaporites at the top of the formation. It contains mudrocks that are rich in detrital zircons with of ca. 270‐–245 Ma. The mixed carbonate and siliciclastic sequences of the Middle–Upper Triassic Badong Formation records tectonic uplift at its base, and contains detrital zircons with UPb age peaks at ca. 2500, 1850, 920–800, 450 and 350–220 Ma. Combined with petrographical observations and tectonic subsidence calculation, these detrital zircon UPb ages record a significant provenance change from recycled material derived from the SCB to newly generated detrital material from the NCB. This provenance change records the initial SCB–NCB collision in the eastern Qinling Orogenic Belt during the Early Triassic. •An Early Triassic provenance change was recognized from the Zigui and Dangyang basins.•These basins started to receive sediments from Qinling Orogen during the late Early Triassic.•Tectonic subsidence analysis denotes a basement uplift in the Middle Triassic•Initial collision between South China and North China in eastern Qinling occurred during the Early Triassic.